Pemantauan Kelembaban tanah Berbasis IoT Menggunakan Sensor Soil Moisture - Laksono, Ivan Luthfi; Kynta, Diva Putri; Fadli, Muhammad; Wijaya, Vannes; Hermanto, Dedy (Program Studi Teknik Informatika Universitas Multi Data Palembang, 2024)
Soil is commonly utilized as a substrate for the cultivation of plants. The level of soil moisture has a significant impact on the growth and survival of nearby plants. Flourishing vegetation assimilates water from the soil, thereby impacting soil moisture. In addition, solar radiation induces water evaporation in the soil, leading to its desiccation. Excessively arid soil leads to plant wilting, whereas excessively saturated soil hinders the optimal growth of neighboring plants. This study focuses on the real-time detection of soil moisture using a Soil Moisture sensor. The approach employed in this research is Research and Development. The research process consists of three stages: planning, design, and assessment. The Soil Moisture sensor will collect data on the moisture content of the soil. This data will then be retrieved and documented by the ESP32 device, which will transmit and store it in a Firebase database. Once the data is recorded, it will be showcased on a website developed with the PHP programming language and the Laravel framework. This will allow users to monitor the exhibited information directly. The investigation yielded variations within each category for dry soil 28.5%, moist 58.4%, and wet 68%.